Novel purine thioglycoside analogs: synthesis, nanoformulation and biological evaluation in in vitro human liver and breast cancer models - Abu-Zaied MA; Loutfy SA; Hassan AE; Elgemeie GH (Dove Medical Press, 2019)
Mamdouh A Abu-Zaied,1 Samah A Loutfy,2,3 Ashraf E Hassan,2,4 Galal H Elgemeie41Green Chemistry Department, National Research Centre, Dokki, Giza, Egypt; 2Virology & Immunology Unit, Cancer Biology Department, National Cancer Institute, Cairo University, Cairo, Egypt; 3Nanotechnology Research Center, British University, Cairo, Egypt; 4Chemistry Department, Faculty of Science, Helwan University, Helwan, Cairo, EgyptBackground: A series of novel pyrazolopyrimidine and pyrazololpyridine thioglycosides were synthesized and conﬁrmed via their spectral analyses.Purpose: To evaluate the effect of these anti-metabolic compounds against proliferation of Huh-7 and Mcf-7 as in vitro models of human liver and breast cancers, respectively. Vero cells were used as an example of normal green monkey kidney cells.Methods: The most promising compound was subjected to a nanoformulation by its encapsulation into chitosan nanoparticles to increase its anti-cancerous activity. Nanoformulation was confirmed by TEM and FT-IR to ensure encapsulation and screened for their cytotoxicity against Huh-7 and Mcf-7 cells using MTT colorimetric assay and morphological examination. Genotoxic effect was performed by cellular DNA fragmentation assay. Simulated CompuSyn software (linear interaction effect) was conducted to predict the possible synergistic effect of nanocomposite as anticancerous activity. Apoptotic effect was further analyzed by detection of apoptotic proteins using ELISA assay.Results: The nano preparation was successfully prepared by encapsulation of compound 14 into chitosan nanoparticles, controlled to a size at 105 nm and zeta charges at 40.2 mV. Treatment of Huh-7 and Mcf-7 showed that compound 14 was the most cytotoxic compound on both cancer cell lines where IC50 was 24.59 (9.836 μg/mL) and 12.203 (4.8812 μg/mL) on Huh-7 and Mcf-7 respectively. But IC50 of the nano preparation was 37.19 and 30.68 μg/mL on Huh-7 and Mcf-7, respectively, indicating its aggressiveness on human breast cancer cells as confirmed by DNA fragmentation assay and theoretically by CompuSyn tool.Conclusion: A novel series of pyrazolopyrimidine thioglycosides and pyrazolopyridine thioglycosides were synthesized. Nanoformulation of compound 14 into chitosan nanoparticles demonstrated anticancer activity and can be used as a drug delivery system, but further studies are still required.Keywords: purine thioglycoside analogs, chitosan nanoparticles, human breast cancer cells, human liver cancer cells, anticancer agents, antimetabolites